2019
DOI: 10.1080/13563467.2019.1613349
|View full text |Cite
|
Sign up to set email alerts
|

The 2014–15 Financial Crisis in Russia and the Foundations of Weak Monetary Power Autonomy in the International Political Economy

Abstract: This article contributes to international political economy debates about the monetary power autonomy (MPA) of emerging market and developing countries (EMDs). The 2014-15 Russian financial crisis is used as a case study to explore why an accumulation of large international reserves does not provide protection against currency crises and macroeconomic adjustments in EMDs. The analysis centres on the interplay between two dimensions of MPA: the Power to Delay and the Power to Deflect adjustment costs. Two struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Viktorov used the GARCH-MIDAS model to study the relationship between industry volatility and macroindustry, and the results show that both the level and change of income value are positive. e level of CPI, the level of exchange rate, and the constant fluctuation have all had a negative impact on the exchange rate of China's bulk commodities [10].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Viktorov used the GARCH-MIDAS model to study the relationship between industry volatility and macroindustry, and the results show that both the level and change of income value are positive. e level of CPI, the level of exchange rate, and the constant fluctuation have all had a negative impact on the exchange rate of China's bulk commodities [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Formula (10), α, β are parameters, α > 0, β > 0, and α + β < 1. τ t represents the long-term component of volatility. e realized volatility RV t is used to model the longterm component τ t , which is expressed as follows:…”
Section: Garch-midas Modelmentioning
confidence: 99%
“… 6 Global financial crisis in 2007–2009, European debt crisis in 2010–2012 ( Akhtaruzzaman, Abdel-Qader, Hammami, & Shams, 2019 ), Russian financial crisis in 2014–2015 ( Viktorov & Abramov, 2020 ), Chinese stock market crash in 2014–2015 ( Jian, Wu, & Zhu, 2018 ). …”
mentioning
confidence: 99%
“…While the population trend reversed for a short period in the mid-2010s, birth rates are once again insufficient to meet or exceed death rates. 2 In addition to this, Russia was hit by the global recession in 2008, and though it was predicted that the natural resource reserves would allow the economy to recover quickly, a renewed financial crisis began in 2014, when the rouble lost value quite rapidly and the price of oil declined as a result (Desai 2010;Viktorov and Abramov, 2019). Historian and legal studies scholar Marianna Muravyeva (2018) has demonstrated that Russia's ongoing economic crises have given the State the opportunity to scapegoat feminism and "non-normative" sexualities, blaming them for negative demographic outcomes.…”
Section: Constructing the Crisismentioning
confidence: 99%